Marketing Politik Partai Islam Progressif Dalam Perspektif Kaidah Dar’u al-Mafasid Muqaddamun ‘Ala Jalb al-Mashalih - Hawari, Nadirsah Hawari (Faculty of Social and Political Science, Universitas Siliwangi, 2024)
Abstract: This paper discusses the pattern of Islamic political parties' approach to political marketing ahead of the 2019 legislative election in Lampung. This discussion is considered important considering that a political party must continue to maintain its electability on the political stage so that it can continue to be strong in parliament, both central and regional, especially ahead of the 2024 elections. What is meant by progressive Islamic parties in this study is an Islamic party that has a vision, and mission Islam is good and able to adapt quickly to all changes and demands of the times. The problem is, sometimes the spirit to win elections forces party elites or candidates for councillors to justify all means to win and get seats. In the rules of Islamic jurisprudence and political Islam, rejecting harm should take precedence over taking issue (dar'u al-mafasid muqaddamun 'ala jalb al-mashalih) when there is a conflict between the two. The harms of the breakdown of the electoral system and democracy because of the deviant behavior of politicians and the benefit of winning elections must be measured with the right scales. This research is in the form of a field study of elites and candidates from PKS and PAN in Lampung with data sources in the form of questionnaires and interviews. The results of the study found that both PAN and PKS had special strategies to market their respective parties during the 2019 elections such as door-to-door actions, character friendships, delivery of vision and mission, and not unwilling to engage with pragmatic campaign practices such as other parties and candidates because it is considered a mafsadah (damage) in democracy.